If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (43 + -7x) + (83 + -11x) = (117 + -22x) Remove parenthesis around (43 + -7x) 43 + -7x + (83 + -11x) = (117 + -22x) Remove parenthesis around (83 + -11x) 43 + -7x + 83 + -11x = (117 + -22x) Reorder the terms: 43 + 83 + -7x + -11x = (117 + -22x) Combine like terms: 43 + 83 = 126 126 + -7x + -11x = (117 + -22x) Combine like terms: -7x + -11x = -18x 126 + -18x = (117 + -22x) Remove parenthesis around (117 + -22x) 126 + -18x = 117 + -22x Solving 126 + -18x = 117 + -22x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '22x' to each side of the equation. 126 + -18x + 22x = 117 + -22x + 22x Combine like terms: -18x + 22x = 4x 126 + 4x = 117 + -22x + 22x Combine like terms: -22x + 22x = 0 126 + 4x = 117 + 0 126 + 4x = 117 Add '-126' to each side of the equation. 126 + -126 + 4x = 117 + -126 Combine like terms: 126 + -126 = 0 0 + 4x = 117 + -126 4x = 117 + -126 Combine like terms: 117 + -126 = -9 4x = -9 Divide each side by '4'. x = -2.25 Simplifying x = -2.25
| x^2-12x-16=0 | | c+160=1780 | | c=1/2(s+b)2 | | 0.8(x+4)-0.3x=1.7 | | (x-4)(x+2)(x+2)=0 | | 4(x+8)=-4(x-4) | | 3k+k-4/9=1/3 | | 2x+4-5(x+1)=4x+5 | | x^4/3=1296 | | -x^2+17x+45=0 | | c=1/2(s+b)f | | 7-5v+10= | | 4x=10x-3 | | 0.25x^2-10x+64=0 | | -1+8p-p=7p-1p | | x^3-8x-16=0 | | 2x+10=4x+12 | | 23=4a-8 | | 24=-8/7x | | G=5/9(p-64) | | 4/x=10/x-3 | | 1/5k-(k+1/5)=1/25(k+1) | | 4/5=-x/25 | | 3(2x+6)=36 | | 3+6x-8x+10=25 | | m-61.8=-10.9 | | a^3+3a-4=0 | | 6y-17=4y+11 | | y=1*5+87 | | .61x=137.86 | | 25x^2-10x-99=0 | | 0=-(g/(2*k^(2)))*x^(2)+(u/k) |